1999
DOI: 10.1021/bi982478+
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 in Caveolae:  Regulation by Protein Kinase Cα and Caveolin-1

Abstract: Caveolae are small plasma membrane invaginations that have been implicated in cell signaling, and caveolin is a principal structural component of the caveolar membrane. Previously we have demonstrated that protein kinase Calpha (PKCalpha) directly interacts with phospholipase D1 (PLD1), activating the enzymatic activity of PLD1 in the presence of phorbol 12-myristate 13-acetate (PMA) [Lee, T. G., et al. (1997) Biochim. Biophys. Acta 1347, 199-204]. In this study, using a detergent-free procedure for the purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
58
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 43 publications
11
58
0
Order By: Relevance
“…The lack of detectable PLD1 in COS cells was not due to a failure of the Ab to detect monkey PLD1 protein, because endogenous PLD1 was readily detected in primary monkey brain tissue and comigrated with baculovirus-expressed recombinant human PLD1. The lack of PLD1 in COS cells has been previously reported with a different anti-PLD1 Ab (48).…”
Section: In Contrast To Phagocytes Cos Cells Express Detectable Pld2supporting
confidence: 56%
“…The lack of detectable PLD1 in COS cells was not due to a failure of the Ab to detect monkey PLD1 protein, because endogenous PLD1 was readily detected in primary monkey brain tissue and comigrated with baculovirus-expressed recombinant human PLD1. The lack of PLD1 in COS cells has been previously reported with a different anti-PLD1 Ab (48).…”
Section: In Contrast To Phagocytes Cos Cells Express Detectable Pld2supporting
confidence: 56%
“…With both cell lines, a proportion of the LPP activity was found associated with the caveolin-enriched domains. Presence of LPP in caveolae/ rafts was anticipated, since studies with other cells have shown that PLD (44,45,127,128) and LPA and S1P receptors (100) can be found associated with DIGs.…”
Section: Lpp In Signaling Platformsmentioning
confidence: 99%
“…Cell specific localization has also been noted with PLD isoforms, where Czarny et al (45) have observed PLD2 is preferentially targeted over PLD1 to caveolae/rafts in Chinese hamster ovary cells, HaCaT human keratinocytes, and U937 cells. Kim et al (127,128), on the other hand, have localized PLD1 to DIGs in 3Y1 rat fibroblasts and COS7 cells.…”
Section: Lpp In Signaling Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that many receptors, signal proteins and enzymes are localized in the caveolae by being anchored through caveolins. These include the epidermal growth factor receptor (7), estrogen receptor (8), insulin receptor (9), Grb 7 (10), c-Src (11), Gprotein (12), protein kinase C (13), phospholipase D (14), nitric oxide synthases (NOS) including the inducible NOS (iNOS) (15,16) and cyclooxygenase-2 (COX-2) (17), among others. Among these proteins known to be associated with caveolins, the expression of NO producing iNOS and prostaglandin producing COX-2 increases by the same oxidative stimuli like the ischemia-reperfusion (5) or exposures to heavy metals (6), heat shock (18) and NO (19) that also cause the induction of HO-1.…”
Section: Introductionmentioning
confidence: 99%